Intergenerationl transmission of unemployment: Causal evidence from Austria - Dominik Grübl; Mario Lackner; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2020)
We estimate the causal effect of parents' unemployment on unemployment among their children in their own adulthood. We use administrative data for Austrian children born between 1974 and 1984 and apply an instrumental variables (IV) identification strategy using parents' job loss during a mass layoff as the instrument. We find evidence of unemployment inheritance in the next generation. An additional day of unemployment during childhood causally raises the average unemployment days of the adult child by 1 to 2%. The greatest effects are observed for unmarried parents, young children, children of low-education parents, and in families living in capital cities. We also explore various channels of intergenerational unemployment, such as education, income, and job matching by parents.
Keywords: J62; J64; 330; intergenerational transmission; mass layoff; unemployment duration; instrumental variable